Investor Sentiment and Mispricing Anomalies - Dai, Jiarui (FEB - Universitas Lampung, 2020)
This paper attempts to investigate the effect of investor sentiment on mispricing anomalies, including value premium, earnings to price, gross profitability, operating profitability, return to assets, and V/P ratio. Via bi-variate analysis and regression analysis, I find these anomalies are stronger in the periods with higher investor sentiment. The effect is robust after controlling for Fama-French three factors. The results are consistent with the idea that investors are more likely to misprice stocks when investor sentiment is high, leading stronger mispricing anomalies in such higher investor sentiment periods. The limitation of this study is that it only includes tests for six misplacing anomalies and does not cover the detection of a large number of anomalies. The value of this study is it is the first study to investigate the effect of investor sentiment on V/P anomaly and to explore these misplacing anomalies as a whole. More importantly, through this study, I actually tested the impact of investor sentiment on investor valuation accuracy.